Stability analysis of dam grouting reinforcement based on FLAC3D - Pengfei Qin (PLoS ONE, 2026)
Ill reservoirs have significant safety hazards, it is urgent to grout and strengthen the dangerous reservoir dams. In order to effectively evaluate the stability of the dam after grouting reinforcement, this paper carried out numerical simulation analysis work. Firstly, the action mechanism of penetration grouting, compression grouting and splitting grouting is described, and it is pointed out that these modes of action are intermixed and interconverted, and they may exist simultaneously in the same grouting process. Next, based on the FLAC3D finite difference program, the analysis and calculation of the stability of seepage control reinforcement of a dangerous reservoir in Guangxi Province were carried out. The calculation results show that, a complete grout curtain zone is formed inside the dam body after grouting reinforcement treatment, the dam stress is adjusted twice, the area of plastic zone decreased 23%, and the stability of the dam body is significantly enhanced. This article has certain guiding significance for the analysis and evaluation of safety and stability of similar projects.